Volume 9: Eighth International Conference on Creep and Fatigue at Elevated Temperatures 2007
DOI: 10.1115/creep2007-26332
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Creep Rupture Strength for New Martensitic 9% Cr Steels

Abstract: The application of new heat resistant steels in power plants requires reliable long term creep rupture strength values as basis for design. Modern martensitic 9% Cr-steels have complex microstructures that change with service exposure. That is why extrapolations of long term strength properties will be most difficult. Due to new long term test results, re-assessments became necessary for grades 911 and 92. Different methods have been used. Good agreement was obtained between a graphical and the numerical ISO 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Subsequently, Viswanathan et al [2,3] recommended 9-12%Cr martensitic stain less steel as the casting material for steam turbine cylinders. Hald [4] and Bendick et al [5] experimentally studied 9-12%Cr mar tensitic stainless steel, containing W, and confirmed that this mate rial met the design requirements for these steam turbine cylinders. Ernst [6], adding B and Co elements to 9-12%Cr martensitic stainless steel, found that the creep rupture strength of 9-12%Cr martensitic stainless steel after 1 x 105 h could reach 90-100 MPa under 6200 °C.…”
mentioning
confidence: 55%
“…Subsequently, Viswanathan et al [2,3] recommended 9-12%Cr martensitic stain less steel as the casting material for steam turbine cylinders. Hald [4] and Bendick et al [5] experimentally studied 9-12%Cr mar tensitic stainless steel, containing W, and confirmed that this mate rial met the design requirements for these steam turbine cylinders. Ernst [6], adding B and Co elements to 9-12%Cr martensitic stainless steel, found that the creep rupture strength of 9-12%Cr martensitic stainless steel after 1 x 105 h could reach 90-100 MPa under 6200 °C.…”
mentioning
confidence: 55%
“…Efforts included testing sponsored by the Metals Properties Council and the U.S. Atomic Energy Commission for all of the materials in the Class 1 components nuclear construction code cases. Further, collection of data from overseas sources was undertaken by Booker and co-workers, among others [11,12]. Booker performed an evaluation of newer data for 304H stainless steel, 316 stainless steel, and alloy 800H [12].…”
Section: Availability Of the Original And Augmented Databases Needed mentioning
confidence: 99%
“…Further, collection of data from overseas sources was undertaken by Booker and co-workers, among others [11,12]. Booker performed an evaluation of newer data for 304H stainless steel, 316 stainless steel, and alloy 800H [12]. He produced a table that summarized the database that produced the ASME III Code Case N-47 stress allowables and compared the database with a new database as shown in Table 6.…”
Section: Availability Of the Original And Augmented Databases Needed mentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies have already been carried out to investigate creep behavior, and oxidation resistant properties of T/P92 steel [3,4,5]. But there has been few information of Proceedings of the ASME Symposium on Elevated Temperature Application of Materials for Fossil, Nuclear, and Petrochemical Industries March 25-27, 2014…”
Section: Introductionmentioning
confidence: 99%